2015
DOI: 10.1038/nn.3913
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory bulb coding of odors, mixtures and sniffs is a linear sum of odor time profiles

Abstract: The olfactory system receives intermittent and fluctuating inputs arising from dispersion of odor plumes and active sampling by the animal. Previous work has suggested that the olfactory transduction machinery and excitatory-inhibitory olfactory bulb circuitry generate nonlinear population trajectories of neuronal activity that differ across odorants. Here we show that individual mitral/tufted (M/T) cells sum inputs linearly across odors and time. By decoupling odor sampling from respiration in anesthetized ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
81
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 48 publications
6
81
2
Order By: Relevance
“…Similarly, we found that MT spike rates -and mean membrane potential -at higher inhalation frequencies were poorly predicted from the inhalation-triggered response at 1 Hz,inconsistent with recent reports of a linear relationship between unitary MT spiking responses and odor stimulus profiles (Gupta et al, 2015). These changes occurred also during 'playback' of sniff bouts recorded from awake mice, strengthening the conclusion that inhalation frequency drives diverse and nonlinear changes in MT excitability in a bottom-up manner during active odor sampling.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Similarly, we found that MT spike rates -and mean membrane potential -at higher inhalation frequencies were poorly predicted from the inhalation-triggered response at 1 Hz,inconsistent with recent reports of a linear relationship between unitary MT spiking responses and odor stimulus profiles (Gupta et al, 2015). These changes occurred also during 'playback' of sniff bouts recorded from awake mice, strengthening the conclusion that inhalation frequency drives diverse and nonlinear changes in MT excitability in a bottom-up manner during active odor sampling.…”
Section: Discussioncontrasting
confidence: 97%
“…At the same time -and in agreement with the results of Gupta et al (Gupta et al, 2015) we found that, with respect to the temporal patterning of MT responses within an inhalation cycle, subthreshold response patterns at higher frequencies (3 and 5 Hz) were, in general, well predicted from those measured at 1 Hz. Simple linear convolution of 1 Hz response patterns could account for substantial transformations of the subthreshold response -including, for example, a shortening of response duration (e.g., Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This surprisingly high frequency is consistent with recent findings that the olfactory bulb circuitry not only enables highly precise odour responses (Cury and Uchida, 2010;Shusterman et al, 2011) but also enables detection of optogenetically evoked inputs with a precision of 10-30 ms (Rebello et al, 2014;Smear et al, 2011). While behavioural and physiological responses to precisely timed odour stimuli have been observed in insects (Brown et al, 2005;Geffen et al, 2009;Nagel et al, 2015;Riffell et al, 2014;Szyszka et al, 2014;Vickers et al, 2001), in mammals the complex structure of the nasal cavity was generally thought to "wash-out" any temporal structure of the incoming odour plume ((Kepecs et al, 2006) see however (Gupta et al, 2015)). Our results show that on the contrary mice can readily make use of information in odour stimuli fluctuating at frequencies of up to 40 Hz.…”
supporting
confidence: 87%
“…404 Such a system could explain that the response dynamics in experiment depend on the 405 task [60,61]. Generally, a better understanding of the temporal structure of the 406 olfactory code [8,[62][63][64][65][66] might allow to derive more detailed models. These could rely 407 on attractor dynamics that are guided by the excitations and thus respond stronger to 408 the early and large excitations [67,68].…”
mentioning
confidence: 99%